The Royal Society of Medicine encyclopedia of family health : the complete medical reference library in one volume - Youngson, Robert (Bloomsbury, 1995)
A complete library on family health giving practical advice on first-aid, nursing sick children, care of the elderly and the maintenance of good health. It gives explanations of the theoretical ideas and concepts underlying modern medicine